2005
DOI: 10.1253/circj.69.576
|View full text |Cite
|
Sign up to set email alerts
|

Combined Effects of Nifekalant and Lidocaine on the Spiral-Type Re-Entry in a Perfused 2-Dimensional Layer of Rabbit Ventricular Myocardium

Abstract: piral-type excitation is the principal mechanism of functional re-entry for the genesis of life-threatening ventricular tachycardia and ventricular fibrillation (VT/VF). 1,2 Nifekalant (NIF) hydrochloride is a new class III antiarrhythmic drug developed in Japan that causes dose-dependent prolongation of action potential duration (APD) in both atrial and ventricular muscle, mainly by reducing the rapid component of the delayed rectifier potassium current (IKr). [3][4][5][6][7] The 2000 American Heart Associati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
21
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 30 publications
2
21
0
Order By: Relevance
“…3 Recently, our coworkers Amino et al conducted a comparative investigation of the 90% APD (APD90) prolonging effect of NIF on the surface of the left ventricle (LV) and APD90 dispersion (APDD) in isolated perfused rabbit hearts at basic cycle lengths (BCLs) of 400 ms and 250 ms. APD90 was prolonged with the efficacy of a reverse use dependent block without increasing the APDD at either BCL, and as a result NIF decreased VT/VF vulnerability. 4 These study results suggest that NIF may stop VT/VF by improving epicardial surface and transmural dispersion of repolarization (TDR) in the LV, in addition to its refractory-period-prolonging action.In a clinical study, we used NIF to treat lidocaine-resistant VT/VF in patients with out-of-hospital cardiopulmonary arrest (OHCPA), and reported that it exerted excellent anti-arrhythmic efficacy. 5 In a study in which we compared OHCPA patients with acidosis and in-hospital cardiopulmonary arrest (IHCPA) patients without acidosis, NIF was Background Because nifekalant hydrochloride (NIF) displayed a superior defibrillating effect on ventricular tachycardia/fibrillation (VT/VF) in cardiopulmonary arrest (CPA) patients, despite some QT prolongation, its effect on transmural dispersion of repolarization (TDR) in the left ventricle (LV) in an animal model of CPA was investigated.…”
mentioning
confidence: 72%
See 1 more Smart Citation
“…3 Recently, our coworkers Amino et al conducted a comparative investigation of the 90% APD (APD90) prolonging effect of NIF on the surface of the left ventricle (LV) and APD90 dispersion (APDD) in isolated perfused rabbit hearts at basic cycle lengths (BCLs) of 400 ms and 250 ms. APD90 was prolonged with the efficacy of a reverse use dependent block without increasing the APDD at either BCL, and as a result NIF decreased VT/VF vulnerability. 4 These study results suggest that NIF may stop VT/VF by improving epicardial surface and transmural dispersion of repolarization (TDR) in the LV, in addition to its refractory-period-prolonging action.In a clinical study, we used NIF to treat lidocaine-resistant VT/VF in patients with out-of-hospital cardiopulmonary arrest (OHCPA), and reported that it exerted excellent anti-arrhythmic efficacy. 5 In a study in which we compared OHCPA patients with acidosis and in-hospital cardiopulmonary arrest (IHCPA) patients without acidosis, NIF was Background Because nifekalant hydrochloride (NIF) displayed a superior defibrillating effect on ventricular tachycardia/fibrillation (VT/VF) in cardiopulmonary arrest (CPA) patients, despite some QT prolongation, its effect on transmural dispersion of repolarization (TDR) in the left ventricle (LV) in an animal model of CPA was investigated.…”
mentioning
confidence: 72%
“…3 Recently, our coworkers Amino et al conducted a comparative investigation of the 90% APD (APD90) prolonging effect of NIF on the surface of the left ventricle (LV) and APD90 dispersion (APDD) in isolated perfused rabbit hearts at basic cycle lengths (BCLs) of 400 ms and 250 ms. APD90 was prolonged with the efficacy of a reverse use dependent block without increasing the APDD at either BCL, and as a result NIF decreased VT/VF vulnerability. 4 These study results suggest that NIF may stop VT/VF by improving epicardial surface and transmural dispersion of repolarization (TDR) in the LV, in addition to its refractory-period-prolonging action.…”
mentioning
confidence: 72%
“…We used a high-resolution optical mapping system to examine the electrophysiological properties of the heart. Details of the system and mapping procedure were described in our previous studies (2,42). In brief, isolated hamster hearts were continuously perfused on a Langendorff apparatus with modified Krebs-Ringer solution equilibrated with 95% O 2-5% CO2 (37°C, pH 7.4).…”
Section: Methodsmentioning
confidence: 99%
“…In a preliminary study, Amino et al investigated the effects of combined NIF and LID administration on the functions of the left ventricle in rabbit hearts using an optical mapping system, and found that the pharmacological actions of NIF (0.5 mol/L) on the spiral excitations of the left ventricle were reversed by LID (3 mol/L). 31 The APD prolongation caused by NIF was readily countered by the concomitant reduction of INa, slow in response to LID; thus, the vulnerability to VF was significantly increased in the presence of both NIF and LID as compared with that in the presence of NIF alone. From also these reasons, LID administration after NIF or concurrent use of LID plus NIF is not recommended.…”
Section: Adverse Reactions Of Nif On the Sinus Node With Concomitant mentioning
confidence: 95%